FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERSEPSI PASIEN TERHADAP PERAN PERAWAT SEBAGAI EDUCATOR DI PUSKESMAS - Gusti Fajri, Sri Wahyu; Erwin, Erwin; Hasneli, Yesi (Coping: Community of Publishing in Nursing; Vol 10 No 5 (2022): Oktober 2022, 2022)
The perception of each individual is different. The perception is influenced by several factors. The factors that influence the perception are divided into two, namely internal factors and external factors. Equalizing the perception of each individual is very important. Nurses as the frontline providers of health services in hospitals and health centers are required to be able to act as educators. This study aims to determine the relationship of factors related to the patient's perception of the nurse's role as an educator in the puskesmas. This study uses a descriptive correlation design with a cross sectional approach. The research sample was 97 respondents with accidental sampling technique. This study uses a questionnaire that has previously been tested for validity and reliability. There was no significant relationship between information (p-value = 0,333), experience (p-value = 1,000) and service (p-value = 0,061) on the role of nurses as educators in puskesmas (p value > 0,05). The factors of information, experience, and patient care were not related to the nurse's role as educator in the puskesmas.